Analysis and design of an ultra-thin metamaterial absorber and its application for in-band RCS reduction of antenna. Issue 5 (24th March 2019) - Sharma, Ankit; Gangwar, Deepak; Kanaujia, Binod Kumar; Dwari, Santanu
ABSTRACT: This paper presents the analysis and design of an ultra-thin metamaterial absorber (MA) for the in-band Radar Cross Section (RCS) reduction of a patch antenna. The proposed MA consists of a periodic array of double square loop structures printed on an FR4 substrate with a thickness of 0.022 λo . A detailed theoretical analysis of the MA unit cell is conducted to investigate the absorbing characteristics of the MA. The simulated and measured results show that MA significantly reduces the RCS of the proposed antenna within its impedance bandwidth and a maximum RCS reduction of 15 dB is achieved at 6.75 GHz. The impedance bandwidth of the proposed antenna is 6.6–7 GHz, which is also improved by the loading of the MA. The results also show that after loading the MA on the patch antenna, the RCS of the proposed antenna is significantly reduced and there is no degradation observed in its radiation properties.